“This is one Lucianus, nephew to the king!:” Political Dynamics of Four Hungarian Translations of "Hamlet" - Almási, Zsolt (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
In this paper I endeavour to retell a partial history of the Hungarian translation of Hamlet’s commentary: “This is one Lucianus, nephew to the King!” (3:2:239) on the “Murder of Gonzago,” aiming to elucidate the intricate interplay between translation, cultural discourse, and socio-political dynamics. Hamlet’s commentary, seemingly straightforward yet laden with complexity, poses implications capable of reshaping the trajectory and purpose of his theatrical experiment, crafted to probe and establish Claudius’ guilt. The partial history of translations encompasses the epochs of Ferenc Kazinczy (18th century) and János Arany (19th century) up to the modern renderings of István Eörsi and Ádám Nádasdy (20th-21st centuries). Within this framework, I claim that exploring these translations of Hamlet’s commentary offers a gauge of Hamlet’s position in Hungarian cultural discourse. The evolving connotations of words, reflective of linguistic shifts, imbue layered meanings not only onto the statement itself but also onto the theatrical experiment it encapsulates. This exploration of translation, interpretation, and linguistic evolution sheds light on Shakespeare’s and Hamlet’s socio-cultural-political role in Hungary, as translations serve not merely as transparent channels of meaning but also as reflections on the political and cultural commitments of translators and their audiences.